2020
DOI: 10.1016/j.cognition.2019.104158
|View full text |Cite
|
Sign up to set email alerts
|

Object features reinstated from episodic memory guide attentional selection

Abstract: When observers search for an object in the environment, they compare the incoming sensory information to the attentional template, a representation of the target in visual working memory (VWM). Previous studies have shown that visual search is more efficient when the attentional template is precise. We pursued the hypothesis that the attentional template in VWM is automatically complemented by features from long-term memory, possibly to increase its precision. At the beginning of the experiment, observers lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 79 publications
2
9
0
Order By: Relevance
“…Specifically, while the matching color may more easily stand-out among non-matching colors due to top-down salience attached to this color, the matching orientation might not be as distinguishable among non-matching orientations. This is consistent with stronger guidance for features that are more distinct [51][52][53][54] .…”
Section: Results Memory Performance Memory Performance Is Illustratsupporting
confidence: 76%
“…Specifically, while the matching color may more easily stand-out among non-matching colors due to top-down salience attached to this color, the matching orientation might not be as distinguishable among non-matching orientations. This is consistent with stronger guidance for features that are more distinct [51][52][53][54] .…”
Section: Results Memory Performance Memory Performance Is Illustratsupporting
confidence: 76%
“…Nevertheless, participants saccaded more often to a distractor that matched the cue's irrelevant color than to a distractor of another color. This effect has already been replicated and extended to the situation where the color is only an attribute of the object stored in long-term memory (LTM) rather than presented during search (Kerzel & Andres, 2020). Moreover, and in line with our results, objects in a search display matching a completely task-irrelevant color belonging to an object contained in VWM can be saccaded to faster and more accurately for a later second task, even in the absence of a distractor (Hollingworth, Matsukura, & Luck, 2013), and can bias the landing position of saccades in the global effect paradigm (Herwig, Beisert, & Schneider, 2010;Hollingworth et al, 2013), and the accuracy and latency of corrective saccades (Hollingworth & Luck, 2009;Hollingworth & Matsukura, 2019).…”
mentioning
confidence: 82%
“…For instance, it has been demonstrated that memory-based interference increased with two “accessory” representations and two corresponding distractors (Chen & Du, 2017 ; Fan et al, 2019 ; Frătescu et al, 2019 ; Hollingworth & Beck, 2016 ). Second, memory-based interference has been reported in conditions where both the attentional template and the “accessory” representation were maintained in WM, which should not occur if the attentional template is the only “active” representation (Bahle et al, 2018 ; Foerster & Schneider, 2018 ; Kerzel & Andres, 2020 ; Zhang et al, 2018 ). Finally, as WM representations are stored in a distributed manner across sensory, parietal, and prefrontal networks (Christophel et al, 2017 ; D'Esposito & Postle, 2015 ; Postle, 2006 ), some argue that a bottleneck limiting attentional guidance to a single representation is unlikely, as that would require a singular, WM-specific neural mechanism (Kristjánsson & Kristjánsson, 2018 ).…”
Section: Wm and Visual Searchmentioning
confidence: 99%
“…However, this conclusion may be compromised by the very nature of the reviewed studies, that is, the use of realistic objects as stimuli. For instance, setting up attentional templates for realistic objects based on visual information may benefit from the reinstatement of object features from LTM (Kerzel & Andres, 2020 ), which may contribute to the advantage of pictorial compared with verbal cues. Moreover, it remains poorly understood whether all features of an object encoded in WM can interact with visual search.…”
Section: Wm Resources and Visual Searchmentioning
confidence: 99%